2017
DOI: 10.1212/wnl.0000000000004214
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of mild traumatic brain injury

Abstract: Given the lack of objective biomarkers and the spectrum of different disorders that likely encompass mTBI, clinicians are encouraged to adopt a probabilistic, rather than definitive, diagnostic and prognostic framework. The relevance of accurately diagnosing and managing the different manifestations of mTBI becomes clear when one considers the overall incidence of the disorder (42 million people each year worldwide), and the different treatment implications for patients with a true neurodegenerative disorder (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
113
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 68 publications
0
113
0
2
Order By: Relevance
“…Previous literature has suggested that there is a wide spectrum of mTBIs. 18 The results reported in the present study indicate that an HHI may be another grade on the concussion spectrum that cannot be captured by standard clinical testing.…”
Section: Discussionmentioning
confidence: 55%
“…Previous literature has suggested that there is a wide spectrum of mTBIs. 18 The results reported in the present study indicate that an HHI may be another grade on the concussion spectrum that cannot be captured by standard clinical testing.…”
Section: Discussionmentioning
confidence: 55%
“…30 It is less clear why a similar spatial shift should result from a diffuse problem like mTBI, which by most definitions excludes focal lesions on imaging. 31…”
mentioning
confidence: 99%
“…Interestingly, Hou and colleagues also reported alterations within auditory and visual networks associated with persistent symptoms. Functional outcome, persistent symptoms, preinjury mental health, psychological mechanisms (e.g., coping), and injury effects are intricately linked in mTBI, and therefore, we realize that measuring functional outcome does not fully capture the patterns of recovery after mTBI (Mayer, Quinn, & Master, ; van der Horn et al, ). However, the Glasgow Outcome Scale Extended is widely used internationally for studying outcome after mTBI, and for the development of prediction models (Nelson et al, ; van der Naalt et al, ).…”
Section: Discussionmentioning
confidence: 99%